Chemical Characterization and Biological Activities of Essential Oil Obtained from Mint Timija Cultivated under Mineral and Biological Fertilizers. (12th November 2017) - Kasrati, Ayoub; Alaoui Jamali, Chaima; Spooner-Hart, Robert; Legendre, Laurent; Leach, David; Abbad, Abdelaziz
Abstract : Cultivation of mint timija ( Mentha suaveolens subsp. timija (Briq.) Harley) constitutes a promising solution to the conservation and sustainable utilization of this Moroccan endemic and threatened species. Optimized agronomic practices require mineral and/or biological fertilizer applications. The aim of this study was to determine the effects of application of a complete (N, P, and K) mineral fertilizer and vesicular arbuscular mycorrhizae (VAM) inoculation on the composition, antioxidant, and insecticidal properties of mint timija essential oils (EOs). The GC-MS analyses identified 27 components representing more than 99.9% of the total oils. Menthone (40.7–49.3%), pulegone (31.3–36.5%), and isomenthone (2.5–4.4%) were found to be the main constituents. Cultivation of mint timija with mineral fertilizer and VAM inoculation induced an increase in menthone content and a parallel decrease of pulegone. Both treatments enhanced the antioxidant activity of the investigated EOs in all assays (IC50 ranged from 2.34 ± 0.03 mg/mL to 6.82 ± 0.25 mg/mL), while no significant difference in the toxicities of these oils against Tribolium confusum du Val. has been observed. Overall, we conclude that cultivation using complete mineral fertilizer and VAM inoculation could be useful in modulating the chemical composition and enhancing the antioxidant activity of the EO of this endemic Moroccan species.